2014
DOI: 10.1002/app.41003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of amphiphobic structural surface thickness in relation to its functionality on stainless steel plates

Abstract: Fluorine-based amphiphobic coatings have been widely used in commercial textiles to provide water-and oil-repelling abilities. However, few reports from the literature survey have discussed the surface structural effects of the coated substrate on amphiphobicity. In this research, various thickness amphiphobic coatings based on mixed epoxy, tetraethylorthosilicate, and a particular alkoxysilane with fluorinated side chains (F-silane) were deposited on Grade 420 stainless steel plates. Film amphiphobicity is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The PLLA powder was fully filled in an aluminum container with an inner diameter of 24 mm and a depth of 3 mm. The details of the sample assembly and the pressure and temperature calibrations were the same as those described in previous article . After loading the sample, low pressure (0.1 MPa) was applied, and the temperature was raised to a predetermined level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLLA powder was fully filled in an aluminum container with an inner diameter of 24 mm and a depth of 3 mm. The details of the sample assembly and the pressure and temperature calibrations were the same as those described in previous article . After loading the sample, low pressure (0.1 MPa) was applied, and the temperature was raised to a predetermined level.…”
Section: Methodsmentioning
confidence: 99%
“…This can be observed by time‐resolved synchrotron small‐angle X‐ray scattering (SAXS). Our group researched the cold crystallization behavior of amorphous PLLA under high pressure and found that the α ′ crystal was formed at a limited temperature and pressure range . Recently, Ru et al utilized a homemade pressuring and shearing device to study the crystalline morphology and structure of PLLA under the coexistence of shear and pressure; they obtained almost an exclusive β ‐form directly from the PLLA melt crystallization .…”
Section: Introductionmentioning
confidence: 99%